PRAWO ODMOWY PRZEKAZANIA INFORMACJI SŁUŻĄCEJ WYKRYCIU NARUSZENIA REGUŁ KONKURENCJI W ORZECZNICTWIE EUROPEJSKIEGO TRYBUNAŁU SPRAWIEDLIWOŚCI - Turno, Bartosz (Wydział Prawa i Administracji UAM, 2009)
The privilege in question has been developed by the Community Courts and it is also known as the “Orkem principle”. It aims to support the undertakings’ right of defence and it amounts to the right of an undertaking not to be compelled by the European Commission to admit involvement in an infringement of the Community competition rules. However, it does not mean that an undertaking has an absolute right to remain silent. The privilege is restricted as undertakings are obliged to answer purely factual questions and to comply with requests for the production documents already in existence. The scope of this privilege is criticised by some scholars. The arguments supporting the criticisms relate to the fact that the present approach does not take into account subsequent developments in the jurisprudence of the European Court of Human Rights. The critics argue that absolute privilege against self-incrimination emanating from the ECtHR’s case law (which is also applicable to undertakings) should be applied to Commission’s competition proceedings as well because these proceedings have been characterised as having a criminal law character leading directly to the imposition of a quasi-criminal sanction(s). Although the Community Courts do attach great value to the case law of the ECtHR and respect the fundamental rights as guaranteed by the Convention on Human Rights, they have so far denied such an extension. Community Courts have taken the view that even taking into account the ECtHR’s jurisprudence, the scope of the privilege should not be widened as competition proceedings which, being administrative in nature, are addressed to economic undertakings and not to natural persons. The existence of the privilege in question in the Polish antimonopoly law should be carefully considered because the provisions of the Convention setting out the rights to a fair trial are directly effective with respect to Poland, and the investigatory tools of the Polish Competition Authority are almost the same as those of the Commission. Therefore, there are reasonable grounds to claim that at least restricted privilege against self-incrimination should be applicable in the antimonopoly proceedings carried out by the Polish Competition Authority.
PRIVILEGE AGAINST SELF-INCRIMINATION WITH RESPECT TO THE EC COMPETITION LAW IN THE JURISPRUDENCE OF THE EUROPEAN COURT OF JUSTICE